2012
DOI: 10.1371/journal.pntd.0001864
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Safety of Praziquantel for Treatment of Intestinal Schistosomiasis in Infants and Preschool Children

Abstract: BackgroundIn 2012 the WHO formally recognised that infants and preschool children are at significant risk of schistosomiasis and qualify for treatment with praziquantel (PZQ). Targeted surveys determining both the performance and safety of this drug are now needed in endemic areas. We have formally assessed parasitological cure and putative side-effects in a prospective cohort of Schistosoma mansoni-infected children (aged 5 months–7 years old) in lakeshore settings of Uganda.Methodology/Principal FindingsFrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 33 publications
3
91
2
1
Order By: Relevance
“…To our understanding, this is the first study in Tanzania mainland to attempt to examine the magnitude of S. haematobium infection in children excluding receiving praziquantel preventive chemotherapy campaigns. Although the prevalence of S. haematobium infection was low (1.9%) and all were light infections, the findings demonstrate that young children contribute to the burden of urinary schistosomiasis in the studied community as demonstrated in other sub-Saharan Africa countries [7,13,[19][20][21][22][23][24][25]. Early childhood infection undoubtedly contributes to pathology among preschool children in endemic areas, thus the finding of 12.0% prevalence of blood in urine indicates a probable cryptic morbidity of damage in the urinary tract due to S. haematobium infection despite the observed low prevalence (1.9%) of patent eggs count, all with a light intensity which is common in preschool age children [26].…”
Section: Discussionmentioning
confidence: 51%
“…To our understanding, this is the first study in Tanzania mainland to attempt to examine the magnitude of S. haematobium infection in children excluding receiving praziquantel preventive chemotherapy campaigns. Although the prevalence of S. haematobium infection was low (1.9%) and all were light infections, the findings demonstrate that young children contribute to the burden of urinary schistosomiasis in the studied community as demonstrated in other sub-Saharan Africa countries [7,13,[19][20][21][22][23][24][25]. Early childhood infection undoubtedly contributes to pathology among preschool children in endemic areas, thus the finding of 12.0% prevalence of blood in urine indicates a probable cryptic morbidity of damage in the urinary tract due to S. haematobium infection despite the observed low prevalence (1.9%) of patent eggs count, all with a light intensity which is common in preschool age children [26].…”
Section: Discussionmentioning
confidence: 51%
“…However, children too young or small for MDA have considerable infection prevalences 5,6 in multiple African countries, where they can be exposed through bathing and other activities, 7,8 and they can be treated with no serious adverse events. [9][10][11][12][13] The morbidity pre-school-aged children (PSAC) experience from infection is not well defined, though: effects are known to include fecal occult bleeding, 14,15 hematuria, proteinuria, 16 ultrasound abnormalities, 17,18 and possibly anemia, 19,20 but clinical implications remain unclear. Thus, although these findings have prompted calls for including PSAC in MDA, 21 a 2010 WHO meeting concluded that more evidence was necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Although cases of schistosomiasis-associated CNS vasculitis and pelvic floor myopathy have been described, a causal relationship was not definitively confirmed [101][102][103][104]. Although randomized trials have demonstrated the benefits of praziquantel for nonneurologic manifestations of schistosomiasis such as intestinal or urinary tract involvement [105][106][107][108][109], the management of neuroschistosomiasis is described only in case series [110][111][112]. For the treatment of CNS involvement, experts recommend praziquantel with concurrent corticosteroids, both to treat neuro-inflammatory sequalae of schistosomiasis, and since anti-parasitic treatment can induce a hypersensitivity reaction with features including headache, hemiparesis, seizure, encephalopathy and cerebellar signs [99].…”
Section: Schistosomiasis (Schistosoma Species)mentioning
confidence: 99%